Using illness narratives to identify community perceptions of trauma and cancer risks in Kuwait - Charles W Cange (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background I set out to investigate whether the Kuwaiti environmental health community believed there were psychosocial and chemical factors that influenced the advent of breast cancer in post--Gulf War Kuwait. # Methods In semi-structured interviews with the Kuwaiti environmental health community, I documented participants\' explanations of the community's diseases. I spoke with 26 community members based on a purposive sampling scheme and analyzed the transcriptions by identifying their illness narratives. Three themes emerged from the data. First, as outlined in the section "Collective Trauma: Violence Embodied," the majority of Kuwaitis were affected by an intense amount of trauma. Indeed, PTSD rates have stayed the same in Kuwait since 1991 (\~20%). # Results In the theme "A Toxic Legacy: War and Chemical Exposures," a common refrain I heard was "Cancer's running like a flu now; every family has a case of cancer." Much higher rates of cancer were reported in the post-conflict period. Third, in "Defining Invisible Risks," individuals expressed disdain for the Ministry of Health's approach to post-conflict health; they reported that it should actively research links between disease and chemical exposures. # Conclusions Kuwaitis found physical health concerns were deemed more legitimate than concerns about mental health. My informants described the administration's lack of transparency or trustworthiness in handling their concerns. They called for a formal investigation into the war\'s toxic effects on future generations of Kuwaitis' health and well-being.